Percepción del turismo en las asociaciones productoras del cacao con fines de posicionamiento de concepto del paisaje cultural en la zona centro de Manabí - Ayala García, Karla Patricia (2022)
The objective of the research was to determine the perception of the members of the cocoa producing associations for the positioning of the concept of cultural landscape. The research was qualitative in nature with a descriptive exploratory approach. For the design of the methodology, 3 phases were proposed: starting with the characterization of the associations through bibliographic and documentary review and field visits supported by a related file, it was established that there are 13 associations in the area, but only 5 of these were studied (Fortaleza del Valle, Valle Noble, Kakawen, Maquita Cushunchic and Comuna la Cantera) that buy and market the product at fair prices where the management and planning deficit was identified. In the second phase, the associations' perception of tourism was assessed, where it was established that both leaders and members, through interviews and surveys, 64% perceive the activity as a development alternative considering that they have the potential to position the cultural landscape. The third stage that contemplates the design of strategies started from the SWOT analysis where six strengths, eight weaknesses, eight opportunities and six threats were identified. Based on this, an associative community management model was structured to implement the 6 strategies linked to the comprehensive training of members, product innovation, generation of technical training, which aim to solve the problems detected in this work and thus position the cultural landscape in Manabí central area.